2016
DOI: 10.1055/s-0042-114038
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Skeletal Maturation in Disorders of Retinoic Acid Metabolism: A Case Report and Focused Review of the Literature

Abstract: Background Nutritional excess of vitamin A, a precursor for retinoic acid (RA), causes premature epiphyseal fusion, craniosynostosis, and light-dependent retinopathy. Similarly, homozygous loss-of-function mutations in CYP26B1, one of the major RA-metabolizing enzymes, cause advanced bone age, premature epiphyseal fusion, and craniosynostosis. In this paper, a patient with markedly accelerated skeletal and dental development, retinal scarring, and autism-spectrum disease is presented and the role of retinoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…We undertook this research to reveal postnatal Rdh10 contributions to atRA function and to assess endogenous atRA actions. Previous studies focusing on specific organs or using vitamin A deficiency models revealed that atRA has widespread impact on metabolism, consistent with organ autonomous effects (15)(16)(17)20,(29)(30)(31)(32). Total Rdh10 ablation impairs the biogenesis of multiple organs, including the pancreas, and causes embryonic lethality between E10.5 and E13, but Rdh10 +/2 mice reportedly were "indistinguishable" from WT (33).…”
Section: Discussionmentioning
confidence: 56%
“…We undertook this research to reveal postnatal Rdh10 contributions to atRA function and to assess endogenous atRA actions. Previous studies focusing on specific organs or using vitamin A deficiency models revealed that atRA has widespread impact on metabolism, consistent with organ autonomous effects (15)(16)(17)20,(29)(30)(31)(32). Total Rdh10 ablation impairs the biogenesis of multiple organs, including the pancreas, and causes embryonic lethality between E10.5 and E13, but Rdh10 +/2 mice reportedly were "indistinguishable" from WT (33).…”
Section: Discussionmentioning
confidence: 56%
“…In family 4, the affected son displayed short stature as well as ASD associated with ID, which did not show in his mother. A recent study reported an individual with a de novo 8.3 Mb microdeletion on chromosome 10q23.2-23.33 associated with accelerated skeletal and dental development, craniosynostosis, retinal scarring, and ASD [26]. The patient displayed elevated levels of total RA metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Raised levels of CYP26 enzymes have also been reported in a range of other cancers including breast, colorectal and head/neck cancers, reviewed [149]. Haploinsufficient microdeletions encompassing the CYP26A1 and CYP26C1-containing chromosomal region has also been reported with differing phenotypes of either optic nerve aplasia or premature skeletal and dental aging combined with retinal scarring and autism [213,214].…”
Section: Cyp26 In Human Genetic Diseasementioning
confidence: 99%